2019
DOI: 10.3390/su11205863
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Divergence of a Rare, Endemic Grass (Elymus breviaristatus) in the Southeastern Qinghai-Tibetan Plateau

Abstract: Elymus breviaristatus is a grass species only distributed in the southeast of Qinghai-Tibetan Plateau (QTP), which has suffered from serious habitat fragmentation. Therefore, understanding patterns of genetic diversity within and among natural E. breviaristatus populations could provide insight for future conservation strategies. In this study, sequence-related amplified polymorphism markers were employed to investigate the genetic diversity and hierarchical structure of seven E. breviaristatus populations fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…We extend a previous study ofE. breviaristatus (Yu et al, 2019), which revealed no significant population-level IBD and ignored the environmental features of habitats, by testing for evidence of IBD and IBE in the patterns of genetic variation. We aimed to determine (a) the level, pattern, and structure of genetic variation among and within E. breviaristatuspopulations across the Tibet and Hengduan Mountains transition zone, (b) the possible climatic factors affecting population genetic diversity, and (c) whether the IBD or IBE model best explained the patterns of genetic differentiation among E. breviaristatus populations.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…We extend a previous study ofE. breviaristatus (Yu et al, 2019), which revealed no significant population-level IBD and ignored the environmental features of habitats, by testing for evidence of IBD and IBE in the patterns of genetic variation. We aimed to determine (a) the level, pattern, and structure of genetic variation among and within E. breviaristatuspopulations across the Tibet and Hengduan Mountains transition zone, (b) the possible climatic factors affecting population genetic diversity, and (c) whether the IBD or IBE model best explained the patterns of genetic differentiation among E. breviaristatus populations.…”
Section: Introductionmentioning
confidence: 85%
“…As many rare species are restricted to the QTP, it is valuable to compare the genetic diversity of these species with that of more widespread congenerics (Wang et al, 2019b). In a previous study, SSR and SRAP markers were used to explore the genetic diversity of seven populations of E. breviaristatus on the Northwest Sichuan Plateau (Gu et al, 2015, Yu et al, 2019. Here, our analyses of EST-SSR data showed that E. breviaristatuspopulations in the transition zone between Tibet and the Hengduan Mountains had lower genetic diversity than congenerics such as E. sibiricus (Ma et al, 2012), E. nutans (Chen et al, 2009, Chen et al, 2013, and E. trachycaulus (Gaudett et al, 2005).…”
Section: Genetic Diversity Of E Breviaristatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The different evolutionary history among geographic populations of P. infestans was supported by the non-association between gene diversity in SSR markers and variances in azoxystrobin resistance ( Figure 6), which is expected to be positively corrected for neutral traits [59]. Furthermore, genetic variation is the main determinant of adaptive ability of species to environments [66], and analysis of genetic variation in species can help us to understand its potential and mechanism of evolutionary adaptation [67]. Our results showed that phenotypic plasticity accounted for~40% of the total phenotypic variation while on average the genetic variation (heritability) accounted for 16% of the variation (Table 1).…”
Section: Evolutionary Processes Driving the Development Of Azoxystrobmentioning
confidence: 93%
“…Although these are wild selfing populations, studies have shown that within-population genetic diversity can be moderate and significant in some of them, and as such they are heterogeneous populations of near-homozygous individual plants. This has been documented in diverse wild populations of grasses, including wild oats in China and the USA [60], Elymus breviaristatus in China [61], Elymus nutans and Elymus sibiricus, important perennial forages, in China [62], Elymus tangutorum, a pasture bunchgrass, in China [63], wild emmer wheat (Triticum turgidum ssp. dicoccoides) in Israel [64], Thinopyrum junceum and Thinopyrum junceiforme in Spain [65], Paspalum dilatatum subsp.…”
Section: Diversity Assurance: Stress-induced Male Sterility Promotes mentioning
confidence: 99%